Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2527/2002.8061690x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus requirement of finishing feedlot calves

Abstract: Dietary P supplied to feedlot cattle is important because an inadequate supply will compromise performance, whereas excess P may harm the environment. However, P requirements of feedlot cattle are not well documented. Therefore, 45 steer calves (265.2 ± 16.6 kg) were individually fed to determine the P required for gain and bone integrity over a 204-d finishing period. The basal diet consisted of 33.5% highmoisture corn, 30% brewers grits, 20% corn bran, 7.5% cottonseed hulls, 3% tallow, and 6% supplement. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Calves were fed 0.16, 0.22, 0.28, 0.34, or 0.40% P. Phosphorus intake ranged from 14 to 36 g/d, or 76 to 190% of NRC recommendations for these animals. Performance and bone mineral content were unaffected by P intake (Erickson et al, 2002). However, plasma inorganic P did respond quadratically with the lowest concentrations observed in steers fed 0.16% P. Feed efficiency was not related to P intake ( Figure 3).…”
Section: Feedlot Beefmentioning
confidence: 80%
“…Calves were fed 0.16, 0.22, 0.28, 0.34, or 0.40% P. Phosphorus intake ranged from 14 to 36 g/d, or 76 to 190% of NRC recommendations for these animals. Performance and bone mineral content were unaffected by P intake (Erickson et al, 2002). However, plasma inorganic P did respond quadratically with the lowest concentrations observed in steers fed 0.16% P. Feed efficiency was not related to P intake ( Figure 3).…”
Section: Feedlot Beefmentioning
confidence: 80%
“…A second experiment was conducted (Erickson et al, 2002) with calves of 265 kg initial weight. The control diet contained 0.16% P and graded levels of P were added as monosodium phosphate.…”
Section: Phosphorusmentioning
confidence: 99%
“…Erickson et al (2002) found values of 8.0 mg dL -1 with different levels of P in the diet (0.22%, 0.28%, and 0.24%) for feedlot steers, but levels changed significantly over time. The increased blood Mg for OD (p = 0.0564) could be attributed to the much larger content of Mg in oats (0.42%) than in corn (0.11%) as reported by NRC (1996).…”
Section: Blood Profile and Rumen Parametersmentioning
confidence: 89%